The current velocity effect of the appearance and performance of Jermal fishing gear - Harisno Harisno; Nofrizal Nofrizal; Isnaniah Isnaniah (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2018)
ABSTRACTThis research was conducted in January 2018 in the fishing gear laboratory, Utilization of Fishery Resources Department, Faculty of Fisheries and Marine, University of Riau. The purpose of this research is to know the effect of the current on the appearance of jermal fishing gear and the ideal current velocity for jermal fishing gear. Measurement of the current velocity in the flume tank at the start of the 5-50 Hz frequency measured using a current meter device, obtained the lowest speed of 2.7cm / sec and the highest 47.2 cm / sec indicates a positive correlation, the higher the frequency used, the more high current velocity generated. The result of this research is the higher the current velocity, the higher the position of the capture device from the bottom of the water, the left and right shift position, the period of up and down movement and the period of left-right movement of the jermal fishing gear and the ideal current velocity for the jermal fishing gear that obtained in this study is 11.1 cm/sec, because at this speed all the capture part is open, and also the value of the movement and the resulting period is small.Keyword: current velocity, jermal fishing gear, flume tank